2021
DOI: 10.1080/0886022x.2021.1914659
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes of peritoneal dialysis between patients after failed kidney transplant and transplant-naïve patients: a meta-analysis of observational studies

Abstract: Purpose: The influence of prior failed kidney transplants on outcomes of peritoneal dialysis (PD) is unclear. Thus, we conducted a systematic review and meta-analysis to compare the outcomes of patients initiating PD after a failed kidney transplant with those initiating PD without a prior history of kidney transplantation. Methods: We searched PubMed, Embase, CENTRAL, and Google Scholar databases from inception until 25 November 2020. Our meta-analysis considered the absolute number of events of mortality, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Peritonitis rate was also similar between the groups in all studies except one [13]. In a meta-analysis, Meng et al [31] concluded that new PD patients with a history of failed…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Peritonitis rate was also similar between the groups in all studies except one [13]. In a meta-analysis, Meng et al [31] concluded that new PD patients with a history of failed…”
Section: Discussionmentioning
confidence: 62%
“…Peritonitis rate was also similar between the groups in all studies except one [ 13 ]. In a meta-analysis, Meng et al [ 31 ] concluded that new PD patients with a history of failed transplant had similar mortality risks as transplant-naïve ones. It is important to note that many previous studies in this area did not match their control group for age and comorbidity load, which may contribute to a better survival in the failed-transplant group [ 10 , 14 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have compared the outcomes of patients initiating PD after failed kidney transplant with incident ESRD patients receiving PD. Although some small studies have shown poor outcomes in failed transplant patients (84,85), larger studies and a meta-analysis have demonstrated similar outcomes, including peritonitis rates, technique, and patient survival (81,(86)(87)(88). One study compared the outcomes of patients who initiated PD after allograft failure with those who initiated HD (89).…”
Section: Pd After Kidney Transplant Failurementioning
confidence: 99%
“…Não existe uma modalidade preferida ao iniciar a diálise após uma falha no enxerto renal, uma vez que tanto a DP quanto a HD parecem ser opções adequadas [7][8][9] . O manejo ideal da imunossupressão em pacientes que iniciam a diálise com um TR malsucedido ainda é incerto, pois os dados nesse campo são escassos.…”
Section: Introductionunclassified